Advanced techniques for postharvest disease detection, control, and quality enhancement in papaya: electronic nose analysis and chitosan-zinc oxide nanoparticle coatings - Khan, Ayesha Ashraf (2025)
Papaya (Carica papaya), a valuable tropical fruit in Malaysia, is highly susceptible to postharvest fungal diseases that can severely affect its quality and lead to economic losses. To address these challenges, this study explored a novel, non-destructive approach using electronic nose (EN) technology, a biosensor capable of detecting quiescent fungal infections by sensing changes in volatile composition, thereby avoiding the invasiveness of traditional methods. Additionally, an eco-friendly and cost-effective edible coating has been investigated as a means to control fungal diseases, providing a comprehensive solution to reduce postharvest losses in papaya.